Multimodal Imaging in Stem Cell Therapy for Retinal Disease - Mi Zheng; Yannis M. Paulus (Photonics)
Stem cell therapy has emerged as a promising approach for treating various retinal diseases, particularly degenerative retinal diseases such as geographic atrophy in age-related macular degeneration (AMD), retinitis pigmentosa (RP), and Stargardt disease. A wide variety of imaging techniques have been employed in both preclinical and clinical settings to assess the efficacy and safety of stem cell therapy for retinal diseases. These techniques can be classified into two categories: methods for imaging stem cells and those for the overall morphology and function of the retina. The techniques employed for stem cell imaging include optical imaging, magnetic resonance imaging (MRI), and radionuclide imaging. Additional imaging techniques include fundus photography, fluorescein angiography, and fundus autofluorescence. Each technique has its own advantages and disadvantages, and thus, the use of multimodal imaging can help to overcome the shortcomings and achieve a more comprehensive evaluation of stem cell therapy in retinal disease. This review discusses the characteristics of the main techniques and cell-labeling techniques applied in stem cell therapy, with a particular focus on the applications of multimodal imaging. Furthermore, this review discusses the challenges and prospects of multimodal imaging in stem cell therapy for retinal disease.